Assessment of exacerbation of Depression in pulmonary tuberculosis patients by using PHQ-9 scale at Tertiary Care Hospital - Mahendra Singh Rathore; Bhaktraj Singh Chauhan; Udita Singh; Nidhi Kaushal Karva; Deepali Pathak (International Journal of Pathogens, 2024)
Context: Depression leads to more dysfunction and stress, which could affect the patient's life condition. Tuberculosis is a leading cause of comorbidity with depression. Those suffering from tuberculosis and depression are at higher risk of bad health-seeking nature, resulting in higher morbidities, drug resistance, and mortality. The relationship is not well established. Aims: To identify multiple variables/ dependent factors affecting depression respectively in tuberculosis patients and check the medication adherence among pulmonary tuberculosis patients using Morisky Scale. Settings and Design: A cross-sectional study was conducted at tertiary care hospital in Udaipur, Rajasthan. Methods and Material: A cross-sectional study was conducted in a tertiary care hospital at Udaipur, Rajasthan, between October 2021- July 2022. The cross-sectional study was performed on people with active pulmonary tuberculosis of 18 years and above who are on anti-tuberculotic medications. Results: The subjects with a mean age of 80.07±17.33 had moderately severe depression, and 52.07±17.3 had severe depression as per the PHQ-9 score. Out of 53 males, 12 were severely depressed, and out of 39 females, 13 had depression. The influence of medication adherence on tuberculosis patients with depression showed a negative correlation i,e; (R= -762). The correlation findings were found to be significant (0.01). Our results were consistent with the expected hypothesis, and finally, a substantial interaction between tuberculosis patients and depression was observed. Conclusions: We noticed a significant association between pulmonary tuberculosis and depression. Also, the study interpreted that low medication adherence to anti-tuberculosis treatment may lead to severe depression.
Keywords: Depression; Major depressive disorder; Medication Adherence; Morisky Medication Adherence Scale; PHQ-9 Scale; Tuberculosis; pulmonary tuberculosis